Interpretation of Detection SARS Cov-2 in Semen - Cennikon Pakpahan; Agustinus Agustinus; Aucky Hinting (Indonesian Andrology and Biomedical Journal, 2020)
Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a virus with a high virulence which cause SARS-CoV-2, a disease with potentially dangerous implications for human health and pandemic. The involvement of other organs in the spread of this virus is still being debated. Considering the presence of (Angiotensin Converting Enzyme-2 (ACE-2) and Transmembrane Serine Protease 2 (TMPRSS2) in the reproductive organs including male reproduction,the male reproductive system possiblity for spreading SARS-CoV-2 should be studied. Reviews: Five studies were reveal the presence of SARS-CoV2 in semen. The reported results are inconsistent. Some of these studies also used unclear methods and procedures, which led to bias in the final results. Ongoing studies are needed to confirm the definite findings before specific recommendations can be made for further management. Summary: There is no definite interpretation of whether SARS-CoV-2 spreads through semen, but protection is still needed when it comes into contact with the semen.